Solar spectral conversion based on plastic films of lanthanide-doped ionosilicas for photovoltaics: down-shifting layers and luminescent solar concentrators - Cardoso, M. A. (2022)
The mismatch between the photovoltaic (PV) cells absorption and the solar irradiance on earth is one of the major limitations towards more efficient PV energy conversion. This aspect was addressed by down-shifting the solar irradiance on Earth through luminescent down-shifting layers based on lanthanide-doped surface-functionalized ionosilicas (ISs) embedded in poly(methyl methacrylate) (PMMA) coated on the surface of commercial Si-based PV cells. The IS-PMMA hybrid materials exhibit efficient solar radiation harvesting (spectral overlap of 9.51019 photonss1m2) and conversion (quantum yield 52%). The direct solar radiation and the down-shifted radiation are partially guided and lost through total internal reflection to the layer edges being unavailable for PV conversion of the coated PV cell. By tuning the down-shifting layer thickness, it also acts as luminescent solar concentrator enabling the collection of the guided radiation by flexible PV cells applied on the borders of the down-shifting layer leading to an enhancement of the PV energy conversion from 5% (in the case of the single-use of the luminescent down-shifting layer) to 13% comparing to the bare PV cell. The overall electrical output of the device resulted in an absolute external quantum efficiency increase of ~32% for the optimized Eu3+-based films in the UV spectral region (compared with the bare PV device, which is among the best values reported so far).